Sociodemographic, environmental and biological factors affecting uses of plants from open ecosystems: Insights for improved livelihoods and biodiversity conservation - Ahoyo, Carlos Cédric; Salako, Kolawolé Valère; Houéhanou, Thierry Dehouegnon; Montcho, Immaculée; Glèlè Kakaï, Romain Lucas; Houinato, Marcel Romuald Benjamin (Frontiers in Conservation Science, 2023)
The sustainable management of open ecosystems requires the committed participation of the neighboring people. Attention should be given to plant species ecology, which conditions the rate of vegetation growth. Sociocultural and ecological factors contribute to both the loss and the conservation of fragile ecosystems. Owing to the importance of traditional medicine in Benin, a focus has been made on the selection of species in this field as a case study for highlighting the factors that drive the selection of plant species in Benin. Further inferences highlight the conservation status of the selected woodlands and savannas. The study assessed the effects of people’s sociodemographic status and species’ ecological parameters on the variation in people’s knowledge associated with species’ usefulness in traditional medicine in Benin. An ethnobotanical survey was conducted through semi-structured individual interviews with 590 specialists in traditional medicine. A conditional inference tree model was combined with a generalized linear model to determine the factors associated with traditional medicinal knowledge (TMK). It was found that TMK varied with informant ethnicity, source of knowledge, membership position, age, instruction level, and professional activity. As for the ecological and species accessibility factors, phytodistrict, mode of reproduction of the species, reasons for the species’ disappearance, availability, and conservation status influenced TMK. When combining the two categories of factors, phytodistrict, habitat of species conservation, source of knowledge, and membership position of the informants were highlighted as the principal factors that influenced TMK. These identified factors should be integrated into a comprehensive management plan for TMK conservation and biodiversity management, and the sustainable use of savanna resources. Through this, sustainable management of open ecosystems, resulting in biodiversity conservation, livelihood improvement, and climate change mitigation, will be achieved. Such a plan should be based on the mix of ethnicities and the diversity of the species’ habitat in each phytodistrict.